Hubungan Karakteristik Sosiodemografi terhadap Tingkat Kepuasan Pelayanan Kefarmasian di Apotek X Kabupaten Cirebon - Like Efriani; Lola kemala dewi; Sri Marfuati (BORNEO JOURNAL OF PHARMASCIENTECH, 2022)
One of the pharmaceutical service satisfaction assessment processes is directly influenced by individual characteristics (patients). The purpose of this study was to determine the relationship between the characteristics of pharmaceutical services at pharmacy X Cirebon district. The design of this study used an observational method with a cross sectional approach. Collecting data using a questionnaire distributed to 109 respondents and analyzed by chi square test. The data obtained were analyzed using SPSS 25. The results of the statistical analysis of patient characteristics showed that the majority were aged 17-25 (39%), majority gender was female (52%), the majority education was SMA/SMK (57%), the majority were other occupations consisting of laborers and farmers (25%). The results of the observational analysis of the level of satisfaction of pharmaceutical services, the majority of respondents stated that they were very satisfied as many as 64 respondents (59%). The results of the correlation analysis showed that service satisfaction was influenced by the patient's age (P<0.05), and the assessment of pharmaceutical service satisfaction was not influenced by gender, education and occupation (P>0.05). The conclusion that can be drawn is that there is a relationship between respondent characteristics and satisfaction with pharmaceutical services at Apotek X, Cirebon Regency.